A new process for green extraction of essential oil from Eucalyptus oleosa: Microwave-assisted hydro distillation - Mehrez Romdhane1; Houcine Bendaoud; Ezzeddine Saadaoui; Walid Elfalleh (Arabian Journal of Medicinal and Aromatic Plants, 2019)
In this work, the potential of microwave-assisted Hydro-distillation (MAHD) process was evaluated for the extraction of Tunisian Eucalyptus oleosa essential oils and the results were compared with those of the conventional Hydro-distillation (HD) in terms of extraction time, essential oil yield, chemical composition, energy consumption and environmental impact. Results show that essential oil obtained by MAHD was quantitatively like those obtained by HD, but MAHD offered net advantages in terms of saving energy and extraction time (90 min against 25 min). In addition, the quality of the essential oil is improved thanks to a 50.42% increase in oxygenates compounds. Scanning electron microscopy (SEM) analyses of E. oleosa tissue structure before and after extraction were used as confirmation that microwave technique was faster than conventional HD. This study demonstrates the effectiveness of MAHD as a quick, green and efficient alternative for the extraction of essential oil from medicinal plants.